Interest in Co-located Reproductive and Sexual Health Services Among Women and Men Receiving Medication for Opioid Use Disorder in an Outpatient Treatment Clinic - Stoltman, Jonathan J. K.; Lander, Laura R.; Patrick, Julie H.; Terplan, Mishka; Jones, Hendrée E. (Frontiers in Psychiatry, 2022)
Introduction: Reproductive and sexual health (RSH) are core components of comprehensive care, yet often omitted in addiction treatment. We characterize knowledge of and interest in RSH services and contraceptive method awareness and use in a rural, Appalachian outpatient clinic. Materials and Methods: Between September 2016 and April 2018, a convenience sample of 225 patients receiving treatment for opioid use disorder at an outpatient buprenorphine/naloxone clinic was collected. Participants completed a cross-sectional RSH survey that included demographics, interest in RSH service integration, contraceptive use, and contraceptive knowledge. Results: A total of 212 people (126 non-pregnant women, 29 pregnant women, and 57 men) completed the survey of whom 45.8% indicated interest in adding RSH services. Services of interest include regular physical exams (44.8%), STI/STD testing (41.0%), and contraception education and administration (38.2%). There were no significant differences between interest in co-located services between women and men [P = .327]. Current contraceptive use was low (17.9%-30.9%) among women and men. Contraceptive method awareness was 43.3% for high efficacy methods and 50.0% for medium efficacy methods. Women and currently pregnant women knew more total, high, and medium efficacy contraceptive method than men (P = .029). Discussion: Both women and men in this sample are interested in co-located RSH services. Current contraceptive use was low among participants. Contraceptive knowledge was lower among men compared to women, and generally low. Providing co-located RSH services may facilitate RSH education, contraceptive method uptake, and promote engagement across various RSH domains.